EFEKTIVITAS MEDIA PUZZLE MATEMATIKA TERHADAP KEMAMPUAN BERHITUNG SISWA KELAS III SD INPRES 12/79 TORO KABUPATEN BONE - -, Sudirman; Rosmalah; Aliyah Rahmadani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine whether there is a difference in students’ numeracy skills before and after the use of the Mathematics Puzzle Media, and how effective this media is in improving the numeracy skills of grade 3 studentat SD Inpres 12/79 Toro, Bone Regency. This study employed a quantitative approach using a pre-experimental design, specifically a One-Group Pre-test-Post-test Design. The sample comprised 25 grade 3 student selected using a saturation sampling technique. Data collection involved tests and student response questionnaires. The results indicated that the mean pre-test score was 53.68, whilst the mean post-test score increased to 72.24. The results of the Paired Samples Test analysis showed that the calculated t-value = 8.202 > table t-value = 2.06390 with a significance level < 0.001, indicating a difference in pupils’ arithmetic skills before and after using the Mathematics Puzzle Media. Students’ responses to the use of the Mathematics Puzzle Media also indicated an ‘excellent’ category with an average percentage of 85%. Thus, the Mathematics puzzle media are effective in improving the arithmetic skills of grade 3 student at SD Inpres 12/79 Toro.